Analisis Swot Sebagai Strategi Pengembangan Bisnis (Studi Kasus Pada Usaha Bengkel Tinjak Motor) - Dian Putri Riri Arinji; Dea Natalia Purba; Putri Purnama Dewi; Rara Baitul Yuli Aprian; Ria Crisna Sianturi; Rama Gita Suci (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the business development strategy of a motorcycle repair shop using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis method. The background of this study is based on the increasing competition in the motorcycle repair shop sector, as well as the need for repair shops to improve service quality and competitiveness. This study uses a qualitative descriptive approach through interviews, direct observation, and documentation to identify internal and external factors that influence repair shop performance. The research results show that Bengkel Tinjak Motor has several key strengths, such as experienced mechanics, a strategic location, good customer relations, and a complete range of spare parts. However, weaknesses remain, such as limited workshop facilities and a lack of digital promotion, which are obstacles that need to be addressed immediately to ensure optimal competitiveness. In terms of opportunities, the growth in motorcycle users and the increasing demand for routine service offer potential for business development. On the other hand, threats such as competition from authorized workshops and changing customer preferences are factors that must be anticipated. Based on the recommended strategies, one of them is the WO (Weakness Opportunities) Strategy which focuses on utilizing workshop facility improvements, gradual investment in modern equipment, implementing a digital-based administration system to increase operational effectiveness, and strengthening digital promotions to reach a wider customer base. and creating a sustainable competitive advantage in the motorcycle repair service industry.